THEORETICAL AND LEGAL PROBLEMS OF PROVISION OF CONSTITUTIONAL RIGHTS OF CITIZENS IN THE PROCESS OF ADAPTATION OF THE LEGISLATION OF UKRAINE TO ACQUIS COMMUNAUTAIRE OF THE EUROPEAN UNION - Юринець, Юлія Леонідівна; Бєлкін, Леонід Михайлович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: the danger of violation of the constitutional rights of citizens in the process of formal implementation of the «European» norms is investigated. There has been a recent occurrence in this area of negative trends. Methods: documentary analysis and synthesis, comparative analysis, objective truth, cognitive-analytical, etc. Results: theoretically examined practical dangers for the rights of citizens of the formal implementation of «European» norms in the legislation of Ukraine are shown. Discussion: this «adaptation» discredits the European choice of Ukraine and the adaptation of Ukrainian legislation to the acquis communautaire of the EU.